Where Do We Go from Here? - Gioia, Dennis A.; Schultz, Majken; Corley, Kevin G. (Academy of Management Review, 2000)
The article presents a commentary on this special edition of “Academy of Management Journal” by three of the authors of one of the articles. The authors take this opportunity to discuss the areas of identity theory that are seemingly closed by the conversations in this issue, and those that have begun. The authors think it essential to begin discussing organizational identity as opposed to individual identity. The authors bemoan the tendency of academic disciplines to become extensions or bastardizations of others, and call for organizational identity theory to establish an identity of its own, one that not only acknowledges its internal origins, but its construct via internal and external interaction.